PERSPEKTIF ISLAM DAN BUDAYA PADA TRADISI BARODAK ADAT PERKAWINAN MASYARAKAT SUMBAWA DI ERA GLOBALISASI - Desmawanti, Rosa; Draditaswari, Silka Yuanti; Widia Nita Kasih, Baiq (Cordova Journal language and culture studies, 2024)
This study examines the Barodak tradition in Sumbawa marriage ceremonies within the context of globalization, focusing on both Islamic and local cultural perspectives. Barodak, a tradition of applying natural-based body scrubs to the bride and groom, has become an inseparable part of the identity of the Sumbawa community. This tradition is not merely a cultural ritual but also reflects religious values that align with the philosophy of Islam, encapsulated in the saying, "Adat Berenti Ko Syara’, Syara’ Berenti Ko Kitabullah" (Tradition should be aligned with religious law, and religious law should follow the holy scriptures). However, modernization poses challenges to the preservation of Barodak. With the rise of globalization, certain elements of the tradition have shifted, including the ritual forms, symbolic meanings, and public perceptions regarding its relevance. This study adopts an ethnographic approach through participatory observation and in-depth interviews, enabling a deeper understanding of the cultural and religious values associated with Barodak. The findings reveal ongoing efforts to preserve the tradition's inherent values despite these changes. Sustaining Barodak requires a continuous approach involving community leaders and members, supported by government initiatives through cultural programs and digital promotion. It is hoped that Barodak will continue to endure as a symbol of the Samawa people’s identity, harmonizing culture and religion.